Preadolescents’ gendered spiritual identities and self-regulation - Bosacki, Sandra Leanne (Journal of beliefs and values, 2011)
Research suggests that self-control or self-regulation may play a role in the connections among spirituality, health, well-being, and social behavior. Within the framework of social-cognitive developmental theory, we explore the question of how do children and adolescents learn to think of themselves as gendered and spiritual beings within the context of social and self-relationships, and learn to have control over their mental and social worlds? Specifically, we discuss how educational and developmental research has furthered discourse about theory, methodology, and practice in spirituality, self-regulation and sociocognitive development. We argue that preadolescents’ understanding of themselves as gendered, spiritual beings is part of a complex, developmental process that is dynamic and co-constructed within a community of body, mind, and spirit. We conclude the discussion with future research questions to guide developmental and educational research with precise, conceptually sound definitions, respectful and accurate research methods, and meaningful dissemination.